Confirming the Explosive Outflow in G5.89 with ALMA - Zapata, Luis A. (2020)
The explosive molecular outflow detected decades ago in the Orion BN/KL region of massive star formation was considered to be a bizarre event. This belief was strengthened by the nondetection of similar cases over the years with the only exception of the marginal case of DR21. Here, we confirm a similar explosive outflow associated with the UCHII region G5.89-0.39 that indicates that this phenomenon is not unique to Orion or DR21. Sensitive and high angular resolution (∼0.″1) Atacama Large Millimeter/submillimeter Array (ALMA) CO(2-1) and SiO(5-4) observations show that the molecular outflow in the massive star-forming region G5.89-0.39 is indeed an explosive outflow with an age of about 1000 yr and a liberated kinetic energy of 1046-49 erg. Our new CO(2-1) ALMA observations revealed over 30 molecular filaments, with Hubble-like expansion motions, pointing to the center of UCHII region. In addition, the SiO(5-4) observations reveal warmer and strong shocks very close to the origin of the explosion, confirming the true nature of the flow. A simple estimation for the occurrence of these explosive events during the formation of the massive stars indicates an event rate of once every ∼100 yr, which is close to the supernovae rate.